Abnormal Laryngeal Electromyography Findings in Asymptomatic Adults Across the Age Spectrum. (30th October 2020) - Leclerc, Andrée‐Anne; Munin, Michael C.; Smith, Libby J.; Rosen, Clark A.
Abstract : Objectives/Hypothesis: Laryngeal electromyography (LEMG) is a diagnostic tool for patients with suspected neurogenic abnormalities of the larynx. LEMG is often used with the assumption that any abnormality is symptom‐/disease‐related. We sought to determine the prevalence of abnormal LEMG findings in a group of healthy asymptomatic adults across a large age spectrum. Study Design: Open, prospective study, gender‐match and age balanced by decade. Methods: Forty‐six healthy participants (age 20–78) underwent LEMG, including 178 muscles. Participants had no history of voice problems, normal VHI‐10, and normal flexible laryngoscopy. Qualitative and quantitative LEMG (bilateral) were performed involving the thyroarytenoid–lateral cricoarytenoid muscle complex (TA‐LCA) and cricothyroid (CT) muscles. LEMG parameters included evaluation for fibrillation potentials, sharp waves, reduced recruitment, polyphasic potentials, electrical synkinesis, and measurement of turns per second. Results: Of participants, 4% had at least one abnormal qualitative finding (slightly reduced recruitment or two to three discrete polyphasic potentials). There were no findings of fibrillation potentials or sharp waves. There were no abnormal qualitative findings in the CT muscles tested. Of participants, 16% had at least one abnormal synkinesis finding. LEMG qualitative abnormalities and quantitative abnormalities do not appear to correlate with gender or age. Conclusion: Abnormal qualitative and quantitative LEMG findings were uncommon and minor in severity in our group of asymptomatic healthy adults. The likelihood of abnormal LEMG results in asymptomatic adults was 2.2% for qualitative findings, 9.3% for synkinesis, and 5.4% for turns/s. Level of Evidence: 3 Laryngoscope, 131:2065–2069, 2021